The Influence of Gross Regional Domestic Product (GDP) and Interest Rates on Investment in West Java Province - Aep Syaeful Millah; Ayus Ahmad Yusuf (Equity: Jurnal Ekonomi, 2024)
Economic growth is significant for every country, where economic growth indicates the success of a country's development. One of Indonesia's efforts to encourage economic growth is by growing the investment sector. Investment is a component that influences the level of aggregate expenditure and is one of the important and main factors in economic development which many economic experts have recognized, according to him there is no development without investment. This research intends to analyze the influence of Gross Regional Domestic Product (GRDP) and interest rates on investment in West Java Province. The data used in this research is secondary data obtained from the Central Statistics Agency (BPS) during 2015-2022 in a time series format. The research method uses a quantitative approach. The data analysis technique was carried out using multiple linear regression in SPSS. The research results show that Gross Regional Domestic Product (GRDP) has a positive and significant influence on investment in West Java Province. Meanwhile, interest rates do not affect investment in West Java Province.